2007
DOI: 10.1063/1.2776005
|View full text |Cite
|
Sign up to set email alerts
|

Exchange coupling between an amorphous ferromagnet and a crystalline antiferromagnet

Abstract: We have investigated the exchange bias effect in bilayers of an amorphous ferromagnet (CoFeB) and a crystalline antiferromagnet (IrMn) in a top-pinned configuration. When the crystalline IrMn layer was deposited on top of the amorphous CoFeB layer, no exchange bias was observed. On insertion of a thin crystalline ferromagnetic layer of NiFe between the amorphous CoFeB and the crystalline IrMn, exchange coupling appeared and it was dependent on the thickness of the NiFe layer. An enhancement in the blocking tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…IrMn with a (111) preferred orientation has been demonstrated to develop a stable AFM spin structure and thereby to exhibit a remarkable EB effect. [19][20][21] In the case of CoPt (5 nm)/FeMn (10 nm), the peak at about 41.5 disappears but another peak at around 43.3 emerges, indicating the lack of the IrMn(111) reflection and the occurrence of FeMn(111) reflections. The shoulder at around 41.5 remains, and is formed by the superposition of CoPt(222) and the left side of the FeMn(111) peak.…”
Section: Resultsmentioning
confidence: 90%
“…IrMn with a (111) preferred orientation has been demonstrated to develop a stable AFM spin structure and thereby to exhibit a remarkable EB effect. [19][20][21] In the case of CoPt (5 nm)/FeMn (10 nm), the peak at about 41.5 disappears but another peak at around 43.3 emerges, indicating the lack of the IrMn(111) reflection and the occurrence of FeMn(111) reflections. The shoulder at around 41.5 remains, and is formed by the superposition of CoPt(222) and the left side of the FeMn(111) peak.…”
Section: Resultsmentioning
confidence: 90%
“…These changes indicate clearly that all H ex , H c and J k values at the NiFe/IrMn interface are directly correlated with the evolution of the /1 1 1S texture developing with NiFe seed layer thickness and the structural phase of IrMn layer. A correlation between exchange coupling and /1 1 1S texture developing with NiFe layer thickness was also reported for the SiO 2 /Cu/CoFeB/NiFe/IrMn top EB system [19].…”
Section: Magnetic Propertiesmentioning
confidence: 75%
“…Consequently, the choice of ULs for the deposition of AF layer becomes crucial. Accordingly, different materials for AF layer as PtMn [3,8], FeMn [7,10,20,21], IrMn [4][5][6]9,[11][12][13][14][15][16][17][18][19]22,24,25] and different ULs [3][4][5][6][7][8][11][12][13][14][15][16][17][18]21,22] deposited using DC and RF magnetron sputtering (DC-MS, RF-MS) and ion beam sputtering [20] were established. In top EB systems, ULs as Ta/NiFe [6], Ta, Cu or Si [7,13,17,20], Cu, Ru or Cu/ Ru [4,5,15] provides the /1 1 1S texture in AF layer, in bottom type EB systems it was induced by Ta/AuCu [3]<...>…”
Section: Introductionmentioning
confidence: 99%
“…Those interfaces can significantly affect the AFM texture development (and the corresponding AFM pinning field and blocking temperature), SAF coupling strength, interface spin-dependent electron scattering, and thus the achievable overall GMR performance. For example, it has been found that the seed layer material selection [9][10][11][12][13], critical seed layer thickness [10,11,14], oxygen impurity content [15] had strong impact on the AFM texture growth, its grain size, and the corresponding GMR ratio of the film stack. Background impurity effect can be more profound when high oxygen-affinity seed layer (like Ta) is used.…”
Section: Introductionmentioning
confidence: 99%